Faktor-Faktor Yang Berhubungan Dengan Motivasi Pasangan Usia Subur Dalam Mengikuti Upaya Pencegahan CA Serviks Melalui Metode Inspeksi Visual Asam Asetat (IVA) Di Uptd. Puskesmas Sangkrah - yupiasari, Beutifina; , Anisa Catur Wijayanti, SKM., M.Epid; , Purwanti, SKM., M.Kes (2015)
IVA is the early detection of cervical Ca because Virus HPV (Human papilloma Virus) by using a simple manner, namely 3-5% acetic acid in inspekulo and be seen with the naked eye examination is painless , easy, cheap and a direct result of information. The purpose of this research is to know what factors are related to the motivation FAC in following cervical Ca prevention efforts through the method of IVA in the UNIT. Clinic Sangkrah. This research is research Observational Analytic with Cross Sectional approach .The population in this research is the FAC examination in the UNIT. Sangkrah clinics in December 2014-2015 April 65 EFA is done using total sampling. The technique of statistical tests using test Chi Square. Results of the study indicate that there is a relationship of motivation against FAC knowledge (p = 0.000; POR = 9.0; 95% CI = 2,849-28,432), no relationship education FAC against motivation (p = 0.006; POR = 3.9; 95% CI = 1,523-10,033), no relationship jobs FAC against motivation (p = 0.001; POR = 3.8; 95% CI = 2,240-17,090), no relationship age FAC against motivation (p = 0,267; POR = 1.9; 95% CI = been-5,050), no relationship support husband FAC against motivation (p = 0,011; POR = 3.8; 95% CI = 1,378-10,689) in the UNIT. Clinic Sangkrah